Public Financial Management and Growth Interaction: Evidence from the Two-Stage Least Square Approach - Saima Ashraf; Dr. Fouzia Jamshaid; Rabia Batool (International Journal of Business and Economic Affairs, 2021)
Financial Management in the Public sector is an essential part of the country’s development process. Public Sector Financial Management (PFM) encompasses the collection and utilization of revenue. Financial Management Reforms are developments and change over time in finance. In this context, the objective of this study is to explore the impact of PFM on output growth in the case of Pakistan. This study also investigates the effect of public sector financial reforms (implemented in the 1990s) on GDP, the proxy of output growth. Tax reforms included in this study to show a structurally different tax pre and post. The time-series data covering the period from 1977 to 2018 has been taken in this study.Econometrics methodology includes Unit root test, Causality test, and Two-Stage Least squares (2SLS). The 2SLS approach is implemented due to endogeneity. There is an existence of reverse causationbetween the variables, which shows that the change in domestic and external debt shows bilateral causality with output growth. The results of 2SLS show that PFM has a promising impact on output growth. In this regard, domestic debt positively and external debt is negatively associated with output. The government spending on social services, community services, economic services, and reforms positively impacted the economy.On the other hand, government expenditure on administration, defense, and transfer of payment results in decreasing output. Therefore, the study concludes that the behavioral trend, the social context, and time limits set for the achievement of set goals must be considered by effective public sector financial management in Pakistan. This paper will help policymakers allocate the limited resources and help in strategic priorities to spur reallocation from lesser to higher priorities to ensure allocation efficiency.